The irrational terrorist and other persistent terrorism myths - Hudson, Darren (Lynne Rienner Publishers, 2020)
Opinion surveys show that what the public assumes it knows about terrorism is at best a badly distorted view. Recalling the "Flat Earth" phenomenon, early misconceptions have become solidified, despite new evidence refuting them. The authors of The Irrational Terrorist discredit these popular myths and misconceptions, providing an accessible overview of the realities of terrorism and liberally illustrating their analysis with case studies. Ranging from the religious and economic backgrounds of individual terrorists to the nature and outreach of terrorist organizations, they offer fact-based, cutting-edge explanations of the motivations and behavior of terrorist groups.